B cells are critical for autoimmune pathology in Scurfy mice. - Aschermann, Susanne; Lehmann, Christian; Mihai, Sidonia; Schett, Georg; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Impaired regulatory T-cell function results in a severe chronic autoimmune disease affecting multiple organs in Scurfy mice and humans with the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. Previous studies have shown that T helper cells but not cytotoxic T cells are critical for the disease pathology. Whether this T-cell subset is responsible directly for tissue inflammation or rather indirectly via the interaction with B cells or myeloid cells is largely unknown. To study this and to identify potential therapeutic targets for this lethal disease we investigated the contribution of B cells to this complex autoimmune phenotype. We show that B cells and the production of autoantibodies plays a major role for skin, liver, lung, and kidney inflammation and therapeutic depletion of B cells resulted in reduced tissue pathology and in prolonged survival. In contrast, the absence of B cells did not impact systemic T-cell activation and hyperreactivity, indicating that autoantibody production by B cells may be a major factor for the autoimmune pathology in mice deficient for regulatory T cells.

Broad requirement for terminal sialic acid residues and FcγRIIB for the preventive and therapeutic activity of intravenous immunoglobulins in vivo. - Schwab, Inessa; Mihai, Sidonia; Seeling, Michaela; Kasperkiewicz, Michael; Ludwig, Ralf J.; Nimmerjahn, Falk (European journal of immunology, 2014)
Intravenous immunoglobulin (IVIg) therapy is widely used to treat a variety of autoimmune diseases including immunothrombocytopenia, chronic inflammatory demyelinating polyneuropathy, and more recently autoimmune skin blistering diseases. Despite this well-documented clinical success, the precise molecular and cellular mechanisms underlying this immunomodulatory activity are discussed controversially. In particular, the clinically relevant therapeutic pathway of IVIg-mediated immune modulation has not been studied in detail. In the present study, we use four independent in vivo model systems of auto-Ab-mediated autoimmune disease to identify a common pathway explaining IVIg activity under therapeutic conditions in vivo. We show that irrespective of the in vivo model system, IVIg activity is strictly dependent on the presence of terminal sialic acid residues and the inhibitory FcγRIIB under preventive as well as therapeutic treatment conditions. In contrast, specific ICAM3 grabbing nonintegrin related 1, previously demonstrated to be essential under preventative treatment conditions, showed a disease-specific impact on IVIg-mediated resolution of established autoimmune disease.

In vivo enzymatic modulation of IgG antibodies prevents immune complex-dependent skin injury. - Mihai, Sidonia; Albert, Heike; Ludwig, Ralf J.; Iwata, Hiroaki; Björck, Lars; Collin, Mattias; Nimmerjahn, Falk (Experimental Dermatology, 2016)
IgG antibodies are potent inducers of proinflammatory responses by cross-linking Fc receptors on innate immune effector cells resulting in tissue injury. The recently discovered enzymes endoglycosidase S (EndoS) and IgG-degrading enzyme (IdeS) of Streptococcus pyogenes are able to modulate the interaction between IgG antibodies and the Fc receptors, by hydrolysis of the glycan associated with the heavy chain of the IgG molecule (EndoS), or cleavage in the hinge region of the heavy IgG chain (IdeS). In this work, we investigated their ability to inhibit damage mediated by skin-bound antibodies in vivo in two different experimental models, the Arthus reaction, and epidermolysis bullosa acquisita, an autoimmune blistering skin disease associated with autoantibodies against type VII collagen. We demonstrate that both enzymes efficiently interfere with IgG-mediated proinflammatory processes, offering a great asset to specifically target pathological IgG antibodies in the skin and holding great promise for future applications in human therapy.

Is COVID-19-associated pulmonary aspergillosis (CAPA) a myth? Frequency of Aspergillus detection from respiratory samples in intensive care unit patients with and without COVID-19 - Kuemmig, T.; Esse, Jan; Herbst, Larissa; Castellanos, I.; Strauss, Richard; Geißdörfer, Walter; Mihai, Sidonia; Rakova, Natalia; Cipa, Franziska; Pflaum, D.; Werblow, M.; Lang, Anne-Katharina; et al. (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

The role of Fc receptors and complement in autoimmunity. - Mihai, Sidonia; Nimmerjahn, Falk (Autoimmunity Reviews, 2013)
Autoantibodies interact with the innate immune system, including the complement network and Fc receptors (FcRs) bearing effector cells, resulting in the induction of tissue injury. It was suggested that these two pro-inflammatory pathways might mediate distinct effector responses, and that only one or the other effector arm may usually dominate an inflammatory response. Recent studies, however, support the notion that autoantibody-induced tissue injury may depend on both, FcRs and selected pathways of the complement network. This review summarizes our current knowledge on the interactions between autoantibodies, FcRs and complement components as essential triggers of tissue injury in autoimmune diseases like rheumatoid arthritis, anti-glomerular basement membrane glomerulonephritis and subepidermal blistering diseases. Manipulation of these connective pathways might be of therapeutic use to control antibody-mediated autoimmune diseases.